Anthropology, Colonialism and the Reflexive Turn: Finding a Place to Stand - Asch, Michael (Anthropologica, 2015)
This paper offers a reflection on the articles in the present thematic section. It focuses in particular on the relationship between the political stance taken by the articles’ authors and the political positioning of anthropologists in the colonial project before the so-called "Reflexive Turn" in the discipline in the late 1960s and early 1970s. To this end, it critically assesses the point of view of those in the discipline who assert that this move presented a radical departure from a disciplinary orientation that until that time had, at best, ignored colonialism and, at worst, actively promoted it by offering evidence of the stance in opposition to it taken by at least some of our more prominent forebears. This paper concludes by indicating that, rather than representing a departure from an earlier orientation to colonialism, the anti-colonial stance taken by the authors of these articles reflects a perspective of long standing in the field.